Analyzing The Presentation Of Geometry Material Based On Bruner's Theory In Mathematics Textbook - Haidar, Dimas Abdi; Hutama, Fajar Surya; Sunardi, Sunardi (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This research aims to know the conformity of presentation based on Bruner’s theory on fourth-grade mathematics textbook. This is qualitative research. The object of research is the material presentation of a fourth-grade mathematics textbook. Based on the analysis of theorem of presentation by Bruner, the facets chapter obtains a percentage of 56% which belongs to the appropriate category. The circumference and width chapter obtains a percentage of 92% which belongs to the appropriate category. The line connection chapter obtains a percentage of 50% which belongs to the appropriate category. The angle measuring chapter obtains a percentage of 56% which belongs to the appropriate category. The overall percentage of the geometry textbook is 64% which belongs to the appropriate category. The percentage of enactive aspects implemented in the presentation of geometry in mathematics textbook is 28%., the percentage of iconic aspects implemented in the presentation of geometry in mathematics textbook is 73%, and the percentage of the symbolic aspect is 56%.